Papers relating to the Ford peace plan
Correspondence, memoranda, speeches, reports, conference proceedings, biographical sketches, bulletins, news summaries, clippings, and other records relating to the Ford International Commission, Henry Ford Peace Expedition, and the Neutral Conference for Continuous Mediation in Stockholm, Sweden. Correspondents include Jane Addams, William Jennings Bryan, David Starr Jordan, Ben B. Lindsey, and S.S. McClure.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Addams, Jane, -- 1860-1935 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Ford, Henry, -- 1863-1947.; Jordan, David Starr, -- 1851-1931 -- Correspondence; Lindsey, Ben B. -- 1869-1943 -- Correspondence; McClure, S. S. -- 1857-1949 -- Correspondence; Ford International Commission; World War, 1914-1918 -- Peace